Giving Logotherapy Counseling to Improve The Comprehension of Self-Potential for Student of Counselling Study Program at Hamzanwadi University - Marfuatun; Musifuddin; Baiq agisni (Simposium Antar Bangsa Seminar dan Workshop)
This study aims to know the influence of Logo therapy counselling to improve comprehension of self-potentialforstudent of first semester of counselling study program. This study used one student who has a low level of comprehension of self-potential taken as a sample. The study design used was a single subject study design with design procedure of A-B.The technique of data collection of this study used a questionnaire. Data obtained from questionnaire was then analysed using a single subject experimental formula by calculating many scores obtained in the baseline phase and calculating the scores obtained in the intervention phase and then combined between the two phases to decide the influence before and after treatment (Logo therapy counselling).The result showed that the baselines phases the average score of 60 and in the intervention phase got an average score of 65. So it can be concluded that there was influence of providing Logo therapy counselling service to improve the comprehension of self-potential for student of first semester of counselling study program.